2015
DOI: 10.2486/indhealth.2014-0259
|View full text |Cite
|
Sign up to set email alerts
|

Assessing real-time performances of N95 respirators for health care workers by simulated workplace protection factors

Abstract: To assess performances of N95 respirators for Health Care Workers (HCWs) in a simulated health-care setting, we measured the Simulated Workplace Protection Factors (SWPFs) in real-time from the volunteers. A total of 49 study subjects, wearing 3 M respirator Model N95 1860 and 1860S, were fit tested using the OSHA Exercise Regimen. The test subjects were asked to perform simulated scenarios, including patient assessments, suction, and intravenous injection (IV) treatment. Two TSI PortaCount instruments continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…A more recent Korean study found that the QNFT pass rate of a single model (3M 1860/1860S) was 73.5%. 7 The pass rate of the same model in another study from China was slightly lower (57.4%-61.3%). 8 Despite a moderate difference in pass rates, our results are in line with those of previous Asian studies reporting low QNFT pass rates.…”
Section: Discussionmentioning
confidence: 86%
“…A more recent Korean study found that the QNFT pass rate of a single model (3M 1860/1860S) was 73.5%. 7 The pass rate of the same model in another study from China was slightly lower (57.4%-61.3%). 8 Despite a moderate difference in pass rates, our results are in line with those of previous Asian studies reporting low QNFT pass rates.…”
Section: Discussionmentioning
confidence: 86%
“…(6) Head or body movements, such as bending at the waist and moving the head up and down, have been identified as factors affecting the simulated WPF. (7) In general, head and body movement may affect the RPD’s fit, and thus, the WPF given that the faceseal leakage often represents the main penetration pathway for particles to enter into an RPD. (7,9) The between-activity variation of the WPF TWA(C) value was considerable.…”
Section: Resultsmentioning
confidence: 99%
“…Also before the workplace evaluation, the participating workers were fit tested with the N95 FFR selected for the study (SM is not subjected to fit testing). Consistent with the US OSHA protocol 29 CFR1910.134 (7) , a PortaCount (Model 8020, TSI, Inc., Shoreview, MN) was used for the fit testing. A particle generator (Model 8026, TSI Inc.) was used to provide an ambient aerosol concentration sufficient to perform the fit testing (at least 1000 particles/cm 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary outcomes were the fit factors of the three respirators. Secondary outcomes were adequate protection, which was defined as the percentage of fit factor greater than or equal to 100, as this suggests that the respirator provided proper protection, [16][17][18] the overall fit factor and the preference of respirator. The overall fit factor was calculated from the individual fit factors determined for each test exercise performed by each participant where FFn is the fit factor of n movement of one participant.…”
Section: Discussionmentioning
confidence: 99%